PENGARUH MOTIVASI, PENGEMBANGAN KARIR DAN KOMPENSASI TERHADAP KEPUASAN KERJA KARYAWAN PT. TOZY SENTOSA ( CENTRO LIFESTYLE DEPARTMENT STORE ) CABANG YOGYAKARTA - Rosianawati Lovendah (JURNAL MANAJEMEN, 2015)
This study aims to determine the Effects of Motivation, Career development and Compensation Against Employee Satisfaction of PT Tozy Sentosa (Centro Lifestyle Department Store) Branch of Yogyakarta. This is a descriptive study that aims to explain the research variables, namely motivation, career development, compensation and job satisfaction. In this study population were all employees of PT Tozy Sentosa (Centro Lifestyle Department Store) Branch of Yogyakarta which totaled 65 people. As well as sampling techniques strata sampling, which amounts to 40 people . Based on the results of research conducted, it can be concluded as follows: Results of multiple regression analysis of the Effects of Motivation, Career Development and Compensation Against Employee Satisfaction of PT Tozy Sentosa (Centro Lifestyle Department Store ) Branch of Yogyakarta Is Y = 0.258 + 0.313 X1 + 0.286 X2 + 0.315 X3 +e Motivation on job satisfaction in the t test, t value of 2.358 with variable motivational significance value of 0.024 Therefore, the significance value is less than 5% (0.024 2.84 ) and significance value ( 0.000 < 0.05 ), then the hypothesis is accepted so that it can be interpreted that there is a significant influence jointly between motivation , career development and compensation against complacency employee PT Tozy Sentosa. Keywords : motivation , career development and compensation